Comparison of Serum Uric Acid in Females with and without Gestational Diabetes Mellitus During Pregnancy - Khan, Attia Aziz; Tahir , Rubina; Islam , Fareeda; Hasan, Shabnam; Khan, Muhammad Faisal; Firdous, Nuzhat (Indus Journal of Bioscience Research, 2025)
Background: The widespread occurrence of Gestational diabetes mellitus (GDM) occurs during pregnancy because of glucose intolerance which leads to unfavorable health outcomes for both the mother and fetus. Research shows that serum uric acid exists as a potential metabolic dysfunction marker although these connections to GDM lack consistency. The research sought to assess serum uric acid levels between pregnant women who did or did not have gestational diabetes mellitus as a means to understand its predictive value. Methodology: The case-control analysis took place at Abbasi Shaheed Hospital in Karachi during the six-month period between July and December 2023. The study recruited 100 pregnant women in the third trimester with 50 subjects being GDM cases and 50 having non-GDM status. The researchers employed non-probability consecutive sampling to identify study participants. The analysis of serum uric acid levels occurred through a colorimetric assay. SPSS version 25.0 served as the statistical analysis tool and the groups were examined through independent sample t-tests to detect mean differences in uric acid values. Statistical analysis incorporated age, BMI and other demographic groups for stratification purposes and established a p ≤0.05 threshold as the significance marker. Results and Discussion: The mean serum uric acid level was significantly higher in GDM cases (7.06 ± 0.88 mg/dl) compared to controls (4.76 ± 1.06 mg/dl) (p < 0.001). Age and BMI stratifications confirmed this association. Previous research supports the conclusion that high uric acid levels act as a component leading to insulin resistance and GDM development. Conclusion: The elevated level of uric acid in GDM patients demonstrates potential value as a screening measure. Future research needs to determine both cause-effect relationships and study the potential applications of uric acid assessment for pre-identifying and managing GDM patients.